PERUBAHAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MENGGUNAKAN MEDIA GAMBAR YANG MENGASYIKKAN - Aslamiyah, Suwaibatul; Setyawan, Agung (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Study is based on research conducted with a classroom action research (PTK) approach carried out in 2 cycles. The subjects of this study were teachers and fourth grade students consisting of 9 boys and 11 girls. Data were analyzed descriptively qualitative and descriptive quantitative. The student learning outcomes in cycle I obtained a percentage of completeness of 55% with an average score of 70,6 and 85% with an average score of 86,8 in cycle II. From the results of the study it can be comcluded that the implementation of science learning activities using image media can improve student learning outcomes.